Distribution of soil nitrogen and nitrogenase activity in the forefield of a High Arctic receding glacier. Issue 77 (24th January 2019) - Turpin-Jelfs, Thomas; Michaelides, Katerina; Blacker, Joshua J.; Benning, Liane G.; Williams, James M.; Anesio, Alexandre M.
ABSTRACT: Glaciers retreating in response to climate warming are progressively exposing primary mineral substrates to surface conditions. As primary production is constrained by nitrogen (N) availability in these emerging ecosystems, improving our understanding of how N accumulates with soil formation is of critical concern. In this study, we quantified how the distribution and speciation of N, as well as rates of free-living biological N fixation (BNF), change along a 2000-year chronosequence of soil development in a High Arctic glacier forefield. Our results show the soil N pool increases with time since exposure and that the rate at which it accumulates is influenced by soil texture. Further, all N increases were organically bound in soils which had been ice-free for 0–50 years. This is indicative of N limitation and should promote BNF. Using the acetylene reduction assay technique, we demonstrated that microbially mediated inputs of N only occurred in soils which had been ice-free for 0 and 3 years, and that potential rates of BNF declined with increased N availability. Thus, BNF only supports N accumulation in young soils. When considering that glacier forefields are projected to become more expansive, this study has implications for understanding how ice-free ecosystems will become productive over time.